Kinship and frindship in a trust game with third party punishment - Björn Vollan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
This paper reports on a set of trust games with third party punishment (TPP) where participants are either family members or friends or unrelated villagers. The experimental sessions were carried out in southern Namibia (Karas) and the bordering northern South Africa (Namaqualand). The aim was to test several hypotheses derived from kin selection theory as well as to assess the importance of third party punishment for encounters among family members and friends. Building on Hamilton, (1964) it was proposed by e.g. Madsen et al., (2007) that kinship is the baseline behaviour among humans. Thus, I use kinship as basis for comparison of how we treat friends and unrelated people and when there is the possibility to punish free-riding behaviour. It turns out that kinship is the baseline behaviour when no other features are available to humans. However, a personal exchange among friends that has a third party observer performs better than a personal exchange among family members without third party punishment. Contributions to family members can substantially be increased by third party punishment. Thus, human ability to sustain a norm by punishing freeriders at personal costs could also have played an important role in sustaining co-operation among kin.
Keywords: 330; Trust; field experiment; third party punishment; kinship; friendship